Xanthogranulomatous colloid cyst of the third ventricle: Alter your surgical strategy. Issue 1 (February 2018) - Swaminathan, Ganesh; Jonathan, Gandham E; Patel, Bimal; Prabhu, Krishna
Colloid cysts are the most common benign neoplasms of the anterior third ventricle, mostly located at the level of the foramen of Monro and can often manifest as sudden onset headache or loss of consciousness. These cysts often have a well-defined cyst wall, mucinous or watery intracystic fluid and have a fairly good plane with the surrounding parenchyma. Occasionally, intracystic haemorrhage can lead to xanthogranulomatous inflammatory changes within the cyst resulting in focal thickening of the cyst wall and adhesion to the surrounding structures. Here we describe a case of xanthogranulomatous colloid cyst which is a very rare variant of colloid cyst.